Experimental investigation of vibration damper composed of acoustic metamaterials. (April 2017) - Sun, Liang
Abstract: The membrane type acoustic metamaterials have been recently proposed and described in our research team. The present paper presents the experimental results of the vibration damper composed of acoustic metamaterials attached to a rectangular steel plate with free edges, which can be considered as an application extension of the structure. The results of frequency response function (FRF) of the system show that such vibration dampers could reduce the vibrating plate resonance magnitudes by up to 42 dB (averaging 27.1 dB) while providing overall vibration reduction of 24.7 dB in the frequency range of 100–1200 Hz, in comparison with the response of the free plate. However, the mass ratio between the structure and the plate is about 6.1%. Thus, the measurements demonstrate the possibility of its use in practice, such as the aerospace vehicles. Besides this, the vibration reduction experiment of a commercial rubber plate is also conducted, for the comparison purpose with the acoustic metamaterials structure. The final comparison results indicate that the performance on the vibration absorption of the 4 stacked samples is even better than the commercial rubber plate either in the relatively lower frequency range (100–500 Hz) or in the relatively higher one (500–1200 Hz).